2002
DOI: 10.1200/jco.2002.06.039
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Treatment With Epirubicin and Vinorelbine in Metastatic Breast Cancer

Abstract: The epirubicin-vinorelbine combination with G-CSF support has been shown in this study to be highly active as first-line treatment of metastatic breast cancer patients, with significant although transient toxicity. This justifies further evaluation in the neoadjuvant setting and in early-stage breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…We found that the regimen was very active even in patients previously treated with adjuvant or neoadjuvant chemotherapy or having visceral metastases. The toxicity was manageable and compares favorably with that of other regimens (see table 3) [28, 29, 30, 31, 32, 33, 34]. The treatment was administered on an outpatient basis and the majority of patients did not require G-CSF support.…”
Section: Discussionmentioning
confidence: 89%
“…We found that the regimen was very active even in patients previously treated with adjuvant or neoadjuvant chemotherapy or having visceral metastases. The toxicity was manageable and compares favorably with that of other regimens (see table 3) [28, 29, 30, 31, 32, 33, 34]. The treatment was administered on an outpatient basis and the majority of patients did not require G-CSF support.…”
Section: Discussionmentioning
confidence: 89%
“…vinorelbine and epirubicin in the first-line treatment of MBC is rather extensive based on several phase II studies (Chadjaa et al, 1993;Ezzat et al, 1996;Baldini et al, 1998;Tabiadon et al, 1998;Nistico et al 1999;Vici et al, 2002) and a phase III study conducted by the Danish Breast Cancer Group (DBCG) (Ejlertsen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…vinorelbine was generally given at 25 mg m À2 on days 1 and 8 (Chadjaa et al, 1993;Ezzat et al, 1996;Baldini et al, 1998;Tabiadon et al, 1998) or on days 1 and 5 (Vici et al, 2002) of every 3-week cycles. Epirubicin was combined on day 1 of cycles at doses ranging from 60 to 100 mg m À2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest activity of this drug has been observed in patients with non-small-cell lung cancer [7,10,18] and advanced breast cancer [1,8,17]. Short-duration and non-cumulative granulocytopenia is the major dose-limiting toxicity and is rated as moderate to severe in 30% to 40% of patients.…”
Section: Introductionmentioning
confidence: 98%